Phytoestrogens levels determination in the cord blood from Malaysia rural and urban populations - Mustafa, A.M.; Malintan, N.T.; Seelan, S.; Zhan, Z.; Mohamed, Z.; Hassan, J.; Pendek, R.; Hussain, R.; Ito, N. (2007)
This study is a result of an analysis of free and conjugated phytoestrogens daidzein, genistein, daidzin, genistin and coumesterol in human cord blood plasma using LCMS. Cord blood was collected from urban and rural populations of Malaysia (n = 300) to establish a simple preliminary database on the levels of the analyzed compounds in the collected samples. The study also aimed to look at the levels of phytoestrogens in babies during birth as this may have a profound effect on the developmental process. The sample clean up was carried out by solid-phase extraction using C18 column and passed through DEAE sephadex gel before analysis by LCMS. The mean concentrations of total phytoestrogens were daidzein (1.4 ± 2.9 ng/ml), genistein (3.7 ± 2.8 ng/ml), daidzin (3.5 ± 3.1 ng/ml), genistin (19.5 ± 4.2 ng/ml) and coumesterol (3.3 ± 3.3 ng/ml). Distribution of phytoestrogen was found to be higher in samples collected from rural areas compared to that of urban areas. © 2007 Elsevier Inc. All rights reserved.